DAIRY FARMERS’ GROUP DYNAMICS IN “NEW NORMAL” ADAPTATION (A Study Case in Pujon District) - Helian Thus, Orca Oryza Anantha; Bakhtiar, Ary; Ibrahim, Jabal Tarik; Rahadi, Rahadi (Jurnal AGRISEP, 2022)
Dairy farming in East Java, particularly in Malang Regency, is supported by several districts such as Karangploso, Ngantang, Ngajum, and Pujon as the dairy production centers. Pujon district is one of the dairy production centers in Malang Regency, reaching 20,411 cattle. This research aims to describe the dairy farmers’ group dynamics condition and determine its group dynamics level. The location was purposively determined by considering the dairy center area in Malang Regency, where the majority population is dairy farmers. The researcher used the descriptive analysis method and selected 50 respondents by Purposive Sampling. The data were collected using a structured questionnaire, interview, observation, and documentation. Furthermore, the results showed that the majority of group dynamics is categorized as “high,” yet only two elements are categorized as “moderate,” namely group structure (70.3%) and group training and development (70,4%). In this view, the high number of group dynamics showed pride and satisfaction with their work performance regarding achieving the group’s goals. Also, good leadership will improve group effectiveness.